Innovation and valorization in supply chain network - Luigi Cembalo (Agricultural and Food Economics, 2015)
Organizations, institutions and new governance mechanisms are taking place in the domain of innovation and valorization of the agrifood sector. Though not new in the literature, this topic is capturing the interest of scholars. It refers to the analysis of new organizations and governance frameworks in the agribusiness. Since this subject needs a deeper analysis, a platform of scientific-based discussion has been built, namely through the eleventh conference of the Wageningen International Conference on Chain and Network Management (WICaNeM) that was held in Capri (Italy) in June 2014 thanks to joining forces of three universities: Wageningen (NL), Bonn (DE) and Naples Federico II (ITA). WICaNeM is a well-known conference concerning management, economics, innovation, valorization and organization of chains and networks in a Life Sciences context. Thanks to Agricultural and Food Economics journal the 2014 conference benefits of a special issue where a selection of five papers were selected. In this short paper a brief presentation of those papers is provided.
Keywords: 330; WICaNeM; Governance mechanism; Agribusiness